Identification of CTX-M Gene Resistance on Bacteria Acinetobacter baumannii and Klebsiella pneumoniae in Pneumonia Patients in Haji Adam Malik Center Hospital, Medan, Indonesia - S, Safrina; Harahap, Urip; Ginting, Fransiscus (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: To find out whether Acinetobacter baumannii and Klebsiella pneumoniae that cause pneumonia have Ceftriaxon-resistant CTX-M coding genes. Interventions: The method used in this study is a cross sectional prospective design and carried out prospectively in pneumonia patients who have medical record data on the diagnosis of pneumonia patients in the period January to September 2019 at the Haji Adam Malik General Hospital in Medan by taking sputum from the patient, then detected using Polymerase Chain Reaction (PCR) in the Integrated Laboratory of the Faculty of Medicine, Universitas Sumatra Utara. Main outcomes measure: The resistance coding gene in Klebsiella pneumoniae with the percentage of CTX-M gene is 93.7% and Acinetobacter baumannii has a low percentage where the expression of CTX-M gene is 17.6%. Conclusion: The distribution of the CTX-M gene in Klebsiella Pneumoniae is higher than that of Acinetobacter baumannii.